Memetics and Filmmaker Habitus in the Indonesian Film Industry - Hadibroto, Joko Utomo; Nurdiansyah, Dian (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
Typically, film companies produce films that are ready for distribution to cinemas. Film work is the result of collective work. Starting from the involvement of producers, directors, screenwriters, cameramen, and editors, to artistic stylists (production team) through pre-production, production, and post-production processes. Although it is not uncommon to find that film works are not single and sterile works of replication or imitation, which refer to patterns and systems - including film production management and its entities - that have been previously established as a cultural industry. For this reason, the author uses the concept of Meme initiated by Richard Dawkins and synthesized with Pierre Bourdieu's sociological concept, namely: (Habitus x Capital) + Domain = Practice, as well as the cultural industry. The cause of film workers imitating previous works is the rationale for researching the film industry, especially in Indonesia. This research aims to prove that the phenomenon of memetics and habitus seneas occurs in the film industry in various countries, both developed and developing countries. To achieve this goal, the method applied in this research is the descriptive qualitative method. Data is obtained from documentation in the form of film works, especially the film Gundala, which involves the production team. The results of the analysis show that there are memetics and habitus of filmmakers in the film industry. This can be found in a number of production houses that carry out the practice, including Jagad BumiLangit, Falcon Pictures, and Screenplay. Almost every film work is imitative. The implications of this imitation can also be found in several cases of imitation of film works; in Hong Kong, Taiwan, Thailand, India, Japan, Europe, and America. To cite this article (7th APA style): Hadibroto, J. U. & Nurdiansyah, D. (2023). Memetics and filmmaker habitus in the Indonesian film industry. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(1), 30-41. https://doi.org/10.36782/jcs.v13i1.2385